近代日本の官舎建築に関する歴史的研究 - 崎山 俊雄; 飯淵 康一; 永井 康雄; 安原 盛彦 (住宅総合研究財団研究論文集, 2007)
In this paper, we tried to clarify how the supply-system and plane of the official residence had transformed through the modern times . As the result, we clarified that the official residence system had been progressed while closely relating to a political trend as formation of new order to revolution of restoration and so on. And we also crarified, from the hierarchy corresponding to the grading of the official residence and from various attempts through transition processes, that we are able to know the official residence is strongly related to the modern society, and the modern housing is very various coetaneous. 本研究では，我が国近代の官舎建築を取り上げ，供給制度の変遷と住宅平面の具体的様態とを明らかにし，その建築史的意義について検討することを試みた。官舎制度は，維新の大変革に対する新たな秩序の形成や，地方への支配制度の拡大，行政機構の拡大や精緻化といった政治的動向とも密接に関係しながら展開されてきたことが知られた。またその平面に示される職階に応じた相対的な階層構造や平面計画理念，その変遷の過程に認められる様々な試みには，官舎と近代社会との分ち難い結び付きが，また近代住宅における同時代的な多様性が見出され得ることを明確にした。